Student’s Perception on Learning Materials and Learning Strategies of Writing Class - Nadya Nurhidayah Nurdin; Nurfitriyah Halim (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
This paper is a case study research which aims to explore student‟s perception in writing class and the final project. In obtaining the data this research use survey or field research will be applied as the method to collecting the students‟ perceptions towards the learning materials and the learning strategies in Writing Class (WRC) for thesis writing. The survey will be applied to make the generalization of students‟ behavior, facts, and claims as a population. At this research, the sample selected were the total population at writing class of English Department at STKIP YPUP Makassar. The finding asserted that the student‟s perception toward the learning material and learning strategies at Writing Class showed positive influence that the application both of Teacher Centered Strategy and Students Centered Strategy in teaching writing gave positive effects to students, it motivated and made the students enjoy in learning writing.